Thrombin Generation as a Method to Identify the Risk of Bleeding in High Clinical-Risk Patients Using Dual Antiplatelet Therapy - de Breet, C. P. D. M.; Zwaveling, S.; Vries, M. J. A.; van Oerle, R. G.; Henskens, Y. M. C.; van't Hof, A. W. J.; van der Meijden, P. E. J.; Veenstra, L.; ten Cate, H.; Olie, R. H. (Frontiers in Cardiovascular Medicine, 2021)
Background Patients using dual antiplatelet therapy after percutaneous coronary intervention are at risk for bleeding. It is unknown whether thrombin generation can be applied to identify patients receiving dual antiplatelet therapy with a bleeding tendency. Objectives To investigate whether thrombin generation measurement in plasma provides additional insight in the assessment of bleeding risk for high clinical risk patients using dual antiplatelet therapy. Methods Coagulation factors and thrombin generation in platelet-poor plasma were measured in 93 high clinical-risk frail patients using dual antiplatelet therapy after a percutaneous coronary intervention. During 12-month follow-up, clinically relevant bleedings were reported. Thrombin generation at 1 and 6 months after percutaneous coronary intervention was compared between patients with and without bleeding. Results One month after percutaneous coronary intervention the parameters of thrombin generation, Endogenous Thrombin Potential, peak height and velocity index, were significantly lower in patients with bleeding in the following months compared to patients without bleeding. This difference remained in measurements performed after 6 months. Thrombin generation in the patients’ plasma was strongly dependent on factor II-, V- and VIII- activity and fibrinogen. Conclusion High clinical-risk patients using dual antiplatelet therapy with clinically relevant bleeding during follow-up show reduced and delayed thrombin generation in platelet poor plasma, possibly due to variation in coagulation factors. That way, impaired thrombin-generating potential may be a ‘second hit’ on top of dual antiplatelet therapy that increases the bleeding risk in high clinical-risk patients. Therefore, the thrombin generation test has potential to improve the identification of patients using dual antiplatelet therapy at increased risk of bleeding.